Peran Perguruan Pencak Silat MS Jalan Enam Pengasinan dalam Pembentukan Karakter - Suwandi; Putri, Riska; Putri, Mas Fierna Janvierna Lusie; Tajudin (Jurnal Ilmu Sosial dan Budaya Indonesia, 2024)
This research discusses the role of Pencak Silat MS Jalan Enam Pengasinan in the formation of children's character education through the application of values such as discipline, responsibility and courage. The school, founded by H. Mai'in Bin H.Ki`in, uses specific traditions and rituals as part of its members' education process. A qualitative approach was applied in this study, with data collection through in-depth interviews and observations of trainers and members. The results show that Pencak Silat MS Jalan Enam Pengasinan functions not only as a martial art, but also as an effective tool in shaping positive character, especially in social and cultural aspects. Thus, pencak silat makes a significant contribution in educating young people who have a strong personality and are able to play a constructive role in their social environment.